Implementation of Patient-Specific Quality Control in Radiotherapy Treatments with ArcCheck: Implementación de un control de calidad de paciente específico en tratamientos de radioterapia con ArcCheck - Alva Sánchez, Mirko Salomón (2024)
Introduction: Quality control is essential to ensure safety and prevent errors in the administration of ionizing radiation across various radiotherapy techniques. Objective: To evaluate the performance of the ArcCheck detector with the goal of implementing a specific quality control technique for patients treated with dynamic arc therapy. Methods: Fifty patients treated with 6 MV and 10 MV energies on the Clinac® Varian CX were selected. Doses at the isocenter of each treatment plan were analyzed using a PMMA phantom (30 x 30 x 15 cm³) to validate reference values between the treatment planning system and the ionization chamber. The treatment plans were also recreated using the ArcCheck. Results: The mean dose difference at the isocenter was -0.96% and -1.34% for 6 MV and 10 MV, respectively. The average passing rate of the dose distributions in the gamma analysis exceeded 98.0% for both energies. Conclusion: The results demonstrated good concordance with the TG-119 and TG-218 protocols, supporting the use of the detector for quality control in patient-specific treatments.